2010
DOI: 10.4103/0970-4388.73789
|View full text |Cite
|
Sign up to set email alerts
|

Relation of salivary calcium, phosphorus and alkaline phosphatase with the incidence of dental caries in children

Abstract: Saliva could reflect a caries risk situation was supported by the fact that alkaline phosphatase activity was very much significantly higher in caries prone groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 0 publications
2
21
0
4
Order By: Relevance
“…22,23 While these findings disagree with some studies. 24,25 This study found that higher activity of alkaline phosphatase in the saliva of nursing caries children (6.321±1.792KAU/dl) than that of the caries-free children (5.384±2.11KAU/ dl) with highly significant differences. This study found the positive correlation between salivary alkaline phosphatase activity and dmfs index of nursing caries and statistically at high significant differences.…”
Section: Agementioning
confidence: 85%
“…22,23 While these findings disagree with some studies. 24,25 This study found that higher activity of alkaline phosphatase in the saliva of nursing caries children (6.321±1.792KAU/dl) than that of the caries-free children (5.384±2.11KAU/ dl) with highly significant differences. This study found the positive correlation between salivary alkaline phosphatase activity and dmfs index of nursing caries and statistically at high significant differences.…”
Section: Agementioning
confidence: 85%
“…[45] The reduced saliva flow in DS individuals may be related to the existence of changes in the secretory function of the salivary glands of individuals with trisomy 21 and/or hypotonic muscle. [35,36,[39][40][41][42][43]45] Regarding the pH of the saliva of individuals with trisomy 21, there are some studies in which the values are higher [43] than ordinary people, while others have observed similar [11] or lower values. [39] There are several factors that could influence the results described in the literature, such as the analyses method (as used by each researcher), age of individuals, geographic location, food habits and time of collection.…”
Section: Cariesmentioning
confidence: 99%
“…[36,[39][40][41][42][43] It is agreed almost universally that the salivary flow rate is significantly reduced in individuals with Down syndrome. [13,36,[39][40][41][42][43]] Also, Siqueira et al [39] studied the whole unstimulated and stimulated saliva of people with Down syndrome for 2-5 years and found that salivary buffering capacity of these individuals is increased compared with healthy individuals of the same age. Regarding cariogenic microorganisms, it was reported that in adults and in children with trisomy 21, the lower caries rates was associated with lower levels of Streptococcus mutans in saliva.…”
Section: Cariesmentioning
confidence: 99%
See 2 more Smart Citations